BANKIM’S RAJANI: A STUDY INTO HEALTH AND HUMANITY - Dalai, P.; Dalai, Dhriti Ray (International Journal of Research -GRANTHAALAYAH, 2020)
Though there has been a plethora of books and articles written on Bankim Chandra Chattopadhyay’s eponymous fiction Rajani, what is conspicuous after all these is the necessity of a medical humanities’ perspective into this masterpiece of Chattopadhyay. To fulfill such lacuna in the previous studies, the present article makes a hermeneutical attempt to contextualize Rajani at the backdrop of medical knowledge and medical culture during Colonial India. With this hypothesis, the paper proves how Bankim stirs the public imaginations about human health, hygiene and disability along with their cultural and clinical manifestations and ramifications, especially in colonial Bengal.